Effects of TCM on polycystic ovary syndrome and its cellular endocrine mechanism - Chen, Huize; Deng, Chujun; Meng, Zeyu; Meng, Shengxi (Frontiers in Endocrinology, 2023)
Polycystic ovary syndrome (PCOS) is a reproductive endocrine disease characterized by menstrual disorders, infertility and obesity, often accompanied by insulin resistance and metabolic disorders. The pathogenesis of PCOS is relatively complex, which is related to endocrine disorders of the body to a certain extent. The increase of androgen and luteinizing hormone (LH) is the main cause of a series of symptoms. Traditional Chinese medicine (TCM) has obvious advantages in the treatment of this disease, and has remarkable efficacy. It can effectively reduce the insulin level of PCOS patients, regulate lipid metabolism, increase ovulation rate and pregnancy rate, and has fewer side effects. This article reviews the efficacy and safety of Chinese herb and other TCM (such as acupuncture) in the treatment of PCOS and its complications in recent years, as well as the effect and mechanism on cellular endocrine, in order to providing a new clinical idea for the treatment of PCOS.